Diagnostic Role of Plasma MicroRNA-21 in Stable and Unstable Angina Patients and Association with Aging. (13th April 2020) - Ali Sheikh, Md Sayed
Abstract : The present study explored the clinical value of plasma microRNA-21 as a novel biomarker for early prediction of stable and unstable angina patients and its relationship with aging. A total of 255 participants, 123 patients with chronic stable angina, 82 patients with unstable angina, and 50 healthy subjects, were included in our study. Stable coronary and unstable coronary patients were confirmed following AHA/ACC clinical protocols. Total RNA was extracted from plasma by using miRNA-based TRIzol reagent. Plasma miR-21 expression levels were determined by real-time polymerase chain reaction. To evaluate the diagnosis accuracy, the receiver operating characteristic (ROC) curves were used. Plasma microRNA-21 concentration levels were significantly elevated in stable and unstable angina patients as compared with control subjects P < 0.001 . The area under the ROC curves of circulating microRNA-21 was accurately distinguished in stable angina patients (AUC 0.921) and unstable angina patients (AUC 0.944) from healthy subjects. MicroRNA-21 expression gradually elevated with increasing aging in all the populations. Moreover, the current study also demonstrated that the expression of plasma miR-21 levels was significantly associated with different age groups within healthy subjects and stable and unstable angina patients P < 0.001 . This research finding suggested that plasma microRNA-21 may be considered as a suitable new biomarker for early detection of stable and unstable angina patients, and it has a strong correlation with aging.